Global prevalence patterns and distribution of Vibrio cholerae: A systematic review and meta-analysis of 176,740 samples - Engku Nur Syafirah Engku Abd Rahman; Ahmad Adebayo Irekeola; Abdirahman Hussein Elmi; Wei Chuan Chua; Yean Yean Chan (Journal of Infection and Public Health, 2024)
This global systematic review and meta-analysis of Vibrio cholerae prevalence, covering environmental, food, animal, and human samples, analysed 111 studies from five databases. The meta-analysis, adhering to standard reporting guidelines, revealed a pooled prevalence of 10.6 % (95 % CI; 8.2 – 13.5; I2 = 99.595 %, p < 0.001) from 176,740 samples, including 27,219 cholera cases. Despite significant publication bias (Egger’s test, p = 0.00018), prevalence estimate remained stable in leave-one-out analysis. Subgroup analysis showed prevalence varied by region, with Indonesia highest (55.2 %) and Jordan lowest (0.2 %). Asia continent had the highest prevalence (13.9 %), followed by South America (12.1 %), and lowest in Europe (3.8 %). Environmental samples exhibited the highest prevalence (24.9 %), while human samples had the lowest (7.1 %). The pervasive presence of V. cholerae in environmental resources highlights the persistent risk of global cholera outbreaks, necessitating urgent proactive measures and ongoing surveillance for effective cholera control.